2018
DOI: 10.1111/odi.12850
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic linkage between oral lichen planus and autoimmune thyroid disease

Abstract: A significant number of patients with OLP who are not previously diagnosed with thyroid disease have thyroid parameters that are compatible with hypothyroidism. The expression of thyroid-stimulating hormone receptor in OLP lesions suggests that mechanisms related to autoimmune thyroid disease are involved in the aetiology of OLP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…LP has been associated with a variety of systemic disorders such as alopecia areata, vitiligo, myasthenia gravis, active chronic hepatitis, hypertension, Sjögren syndrome, lupus erythematosus, or thyroid pathology (Alaizari, Al‐Maweri, Al‐Shamiri, Tarakji, & Shugaa‐Addin, ; Barbosa et al, ; Chung et al, ; Kiyani & Shahroz, ; Likar‐Manookin et al, ; Robledo‐Sierra et al, ) Of all the articles included, there are only four, which define part of these alterations as exclusion criteria (Mohsin et al, ; Petrou‐Amerikanou et al, ; Saini et al, ; Van Dis & Parks, ). The remaining studies, with the exception of Al‐Maweri et al () who generically defined “immunologic diseases” as exclusion criteria, do not take into account the possible presence of this type of alterations when forming the study population.…”
Section: Discussionmentioning
confidence: 99%
“…LP has been associated with a variety of systemic disorders such as alopecia areata, vitiligo, myasthenia gravis, active chronic hepatitis, hypertension, Sjögren syndrome, lupus erythematosus, or thyroid pathology (Alaizari, Al‐Maweri, Al‐Shamiri, Tarakji, & Shugaa‐Addin, ; Barbosa et al, ; Chung et al, ; Kiyani & Shahroz, ; Likar‐Manookin et al, ; Robledo‐Sierra et al, ) Of all the articles included, there are only four, which define part of these alterations as exclusion criteria (Mohsin et al, ; Petrou‐Amerikanou et al, ; Saini et al, ; Van Dis & Parks, ). The remaining studies, with the exception of Al‐Maweri et al () who generically defined “immunologic diseases” as exclusion criteria, do not take into account the possible presence of this type of alterations when forming the study population.…”
Section: Discussionmentioning
confidence: 99%
“…[38] In addition, a retrospective study on 9,654 patients with psoriasis demonstrated a significant association between this dermatological disorder and HT. [29,39] HT is also associated with urticaria, [40][41][42] lupus erythematosus, [26,37,43] alopecia areata, [44,45] lichen [19,[46][47][48] and scleroderma. [23] Specifically, in patients with scleroderma presenting with complications in pregnancy, authors found that 53% had thyrotoxicosis due to HT.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it seems there is no “dose response effect” between HT and OLP prognosis (Zhang, Hou, et al, 2022). In fact, some studies reported that in patients affected by both OLP and ATDs, OLP lesions were less severe compared to individuals affected only by OLP (Robledo‐Sierra et al, 2018). At the present, however, there is no evidence in specific clinical features of OLP lesions in HT patients.…”
Section: Discussionmentioning
confidence: 99%